C/EBPβ as a master regulator of inflammasome signaling in neurodegenerative diseases: mechanisms and therapeutic implications - Wang, Ji; Li, Yuan; Xia, Yiyuan (Frontiers in Immunology, 2025)
CCAAT/enhancer-binding protein beta (C/EBPβ), a key transcription factor, plays a central role in regulating inflammasome signaling in neurodegenerative diseases (NDs). This review synthesizes the mechanisms by which C/EBPβ modulates neuroinflammation and its potential as a therapeutic target. We conducted a comprehensive systematic review spanning January 1995 to June 2025, systematically querying Google Scholar and PubMed with the following keywords: neuroinflammation, inflammasome activation, C/EBPβ, therapeutic targeting, and neurodegenerative diseases. C/EBPβ exists in three isoforms-LAP1, LAP2, and LIP-each with distinct functions in inflammasome activation. In Alzheimer’s disease (AD), C/EBPβ drives tau cleavage and Aβ pathology through the AEP axis and exacerbates neuroinflammation by upregulating APOE4. In Parkinson’s disease (PD), C/EBPβ silencing reduces α-synuclein aggregation and dopaminergic neuron loss by suppressing the NLRP3 inflammasome. In Amyotrophic Lateral Sclerosis (ALS), C/EBPβ is hypothesized to contribute to TDP-43-associated inflammasome activation, though this requires further validation. In Multiple Sclerosis (MS), C/EBPβ may influence microglial activation and neuroinflammation, as shown in experimental autoimmune encephalomyelitis models. Modulators of the C/EBPβ-inflammasome axis include endogenous regulators like gut-derived metabolites and pharmacological interventions such as small-molecule inhibitors. Therapeutic strategies targeting C/EBPβ hold promise for mitigating neuroinflammation and neurodegeneration, though challenges remain in achieving isoform-specific targeting and blood-brain barrier penetration. Future directions include CRISPR-based editing and biomarker development for personalized therapies.